A continuous fluorescence displacement assay for BioA: An enzyme involved in biotin biosynthesis - Wilson, Daniel J. (2011)
Cofactor biosynthetic pathways represent a rich source of potential antibiotic targets. The second step in biotin biosynthesis is performed by BioA, a pyridoxal 5′-phosphate (PLP) dependent enzyme. This enzyme has been confirmed as a candidate target in Mycobacterium tuberculosis; however, the current bioassay used to measure BioA activity is cumbersome and low-throughput. Here we describe the design, development and optimization of a continuous coupled fluorescence displacement assay to measure BioA activity. In this coupled assay, BioD converts the product of the BioA–catalyzed reaction into dethiobiotin, which is subsequently detected by displacement of a fluorescently labeled dethiobiotin probe from streptavidin. The assay was further adapted to a high-throughput screening format and validated against the LOPAC library.